1977
DOI: 10.1530/acta.0.0840200
|View full text |Cite
|
Sign up to set email alerts
|

DIURNAL RHYTHM OF 5αANDROST-16-en-3-One AND TESTOSTERONE IN PERIPHERAL PLASMA OF BOARS

Abstract: Testosterone and the boar taint steroid 5\g=a\-androst-16-en-3-onewere determined radioimmunologically in peripheral plasma of 3 boars. A modified extraction procedure for the latter compound was established and its reliability confirmed. Samples of plasma were taken every 30 min during three 48 h periods. Diurnal rhythms of both steroids were found with maximum values (concentrations > mean + 2 sd) occurring twice daily in the afternoon and after midnight. Corresponding nadirs (concentrations < mean \m=-\ 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 4 publications
(8 reference statements)
2
7
0
Order By: Relevance
“…Bovine pituitary preparations were used as the reference standards for prolactin (NIH-P-B3, biological activity 24-1 i.u./mg), for FSH (NIH-FSH-B1, biological activity 0-4 times NIH-FSH-S1) and for LH (IH-17-BP, biological activity 0-9 times NIH-LH-S1). Riley, 1975;Karg et al, 1976;Thibier & Martin, 1975), rams (Katongole, Naftolin & Short, 1974;Sanford, Winter, Palmer & Howland, 1974) and boars (Claus & Giménez, 1977). In agreement with these observations, we have also demonstrated a close relationship between the occurrence of LH peaks and increases in blood testosterone for both bulls in this study.…”
Section: Methodssupporting
confidence: 92%
“…Bovine pituitary preparations were used as the reference standards for prolactin (NIH-P-B3, biological activity 24-1 i.u./mg), for FSH (NIH-FSH-B1, biological activity 0-4 times NIH-FSH-S1) and for LH (IH-17-BP, biological activity 0-9 times NIH-LH-S1). Riley, 1975;Karg et al, 1976;Thibier & Martin, 1975), rams (Katongole, Naftolin & Short, 1974;Sanford, Winter, Palmer & Howland, 1974) and boars (Claus & Giménez, 1977). In agreement with these observations, we have also demonstrated a close relationship between the occurrence of LH peaks and increases in blood testosterone for both bulls in this study.…”
Section: Methodssupporting
confidence: 92%
“…Testosterone concentrations in male peccaries are comparable to those reported for domestic boars, which range from 1 to 8 ng/ml, depending upon breed and handling procedure (Ellendorff et al, 1975;Claus & Giménez, 1977;Edqvist et al, 1980). A significant problem associated with assaying serum testosterone in one sample per month, as in the present study, may be pulsatile hormone release.…”
Section: Discussionsupporting
confidence: 59%
“…). However, Claus & Giménez (1977) and Lundström et al (1978) clearly demonstrated simultaneous variation of testosterone and androstenone. Therefore, shortterm variations are probably lower for A/T ratio than for absolute levels of steroids.…”
Section: Fat Androstenone Concentration and Quantitymentioning
confidence: 94%